Estimating Ireland’s labour share - O'Shea, Dónal (ESRI, 2024)
The labour share of income is a crucial economic indicator that captures income distribution between the factors of production. Its importance as a parameter in macroeconomic models motivates this detailed study of methods for estimating the Irish labour share. International comparisons of the labour share that rely on distorted measures of Irish national income are misleading. Modified gross national income (GNI*) should be used as the denominator for the Irish labour share when conducting international comparisons. The numerator of the labour share is a measure of total compensation for labour, including the labour income of the self-employed. This note evaluates existing methods for imputing the labour income of the self-employed and proposes a new method, which applies a sectoral approach to the common assumption of equal total earnings between employees and the self-employed. Using the proposed method, there is no evidence of a decline in the labour share since 1998.